Convenient and easy access to 2-hydroxycyclopent-2-enones from acylcyanohydrins. Issue 33 (16th August 2019) - Pantin, Mathilde; Bodinier, Florent; Saillour, Jordan; Youssouf, Yassine M.; Boeda, Fabien; Pearson-Long, Morwenna S.M.; Bertus, Philippe
Abstract: A convenient access to 2-hydroxycyclopentenones was designed from acylcyanohydrins, by using titanacyclopropane complexes as nucleophilic partners and an intramolecular aldol condensation in basic conditions. The development of a one-pot procedure allows a step- and atom-economic process, and the use of Grignard reagents other than ethylmagnesium bromide provided valuable 3, 4-disubstituted 2-hydroxycyclopentenones. The utility of the hydroxy group was illustrated by further functionalization of the α-position using palladium-mediated cross-coupling reactions. Graphical abstract: Image 1 Highlights: Original substituted 2-hydroxycyclopentenones.. Titanacyclopropane complexes.